(untitled) (Географический вестник=Geographical bulletin, 2017)
В сфере энергетики продолжено рассмотрение взаимосвязи нефтегазового бизнеса и международных проектов долговременного хранения ядерных материалов. Представлены российские варианты создания ядерных хранилищ и сопутствующих геологических оценок. В частности для Северо-Запада России. GEOLOGICAL, ECOLOGICAL AND POLITICAL ASPECTS OF DEPOSITORY AND REPOSITORY OF NUCLEAR MATERIALS Abstract: This paper presents further consideration of the following interrelation in the energy production sphere: oil and gas business and international projects on the long-term storage of nuclear materials. There are discussed some Russian versions of construction of nuclear depositories as well as corresponding geological assessments. In particular, for the North-West Russia.